GENDER DIFFERENCES OF COGNITIVE AND MOTIVATIONAL PREDICTORS OF STUDENT’S PSYCHOLOGICAL WELL-BEING - Serobyan, A. K.; Grigoryan, A.K.; Khachatryan, N. G.; Yerofeeva , V. G. (Modern Psychology, 2022)
The purpose of this study was to investigate gender differences in cog- nitive and motivational factors of achieving success-predetermining stu- dent’s psychological well-being. The Warwick-Edinburgh Mental Well-Being scale (WEMWBS) was used to measure psychological well-being. The mindset and promotion/prevention regulatory focus were consi- dered as cognitive and motivational predictors. The study was based upon a sample of 415 students (Mage=20.4, SDage=2.568), of whom 63.5% were women. Two regression models were developed separately, for men and women to identify gender differences in factors contributing to psychological well-being. The promotion focus was a significant predictor for men’s psychological well-being. Women’s psychological well-being was determined by growth mindset and promotion focus. The prevention focus negatively predicted women’s psychological well-being. The results of this study replicated the findings of other studies, that promotion focus has a predictive role in psychological well-being, at the same time revealing gender differences in cognitive and motivational factors of achieving success.